Trust, culture and communication: determinants of eye health and care among Indigenous people with diabetes in Australia - Anthony B Zwi; Aryati Yashadhana; Ted Fields; Godfrey Blitner; Ruby Stanley (BMJ Global Health, 2020)
Introduction Our study aimed to identify factors that influence access to eye care and eye health outcomes for remote Indigenous Australians living with diabetes.Methods In collaboration with Indigenous Community-Based Researchers (CBR) and Aboriginal Community Controlled Health Services (ACCHS), a qualitative, participatory action research approach was taken, drawing on Indigenist and decolonising methodologies. The study was undertaken in four remote communities, in the Katherine region, Northern Territory and north-western New South Wales, Australia. Interviews and focus groups were undertaken with Indigenous adults aged ≥40 years living with diabetes (n=110), and primary care clinicians working in ACCHSs (n=37). A series of interviews with CBRs (n=13) were undertaken before and after data collection to add cultural insights and validation to participant accounts. Data were analysed inductively using grounded theory, in-depth discussion and NVivo V.11.Results More than one-third of all patients had little to no knowledge of how diabetes affects eye health. Limited access to health information and interpreters, language barriers, distrust of health providers and services, and limited cultural responsivity among non-Indigenous clinicians, were identified as determining factors in eye health and care.Discussion We outline a need to address gaps in trust and communication, through increased access to and resourcing of Indigenous language interpreters and cultural brokers, understandable and culturally sensitive diabetic eye health information and cultural responsivity training for non-Indigenous clinicians. Centring Indigenous cultures in healthcare practice will enable a shared understanding between clinicians and Indigenous patients, and subsequently more equitable eye health outcomes.